ACTIVATION OF ERK BY SONIC HEDGEHOG INDEPENDENT OF CANONICAL HEDGEHOG SIGNALLING - Chang, Hong (2010)
Hedgehog (Hh) signalling is mediated through the Patched-1 (Ptch1) receptor. Hh-binding to Ptch1 blocks the inhibitory effects of Ptch1 on the activity of the transmembrane protein, Smoothened (Smo), resulting induction of target genes by the Gli-family of transcription factors. We demonstrate here that Hh-binding to Ptch1 stimulates activation of Erk1/2. This activation is insensitive to the small molecule Smo antagonists and occurs in a cell line that does not express Smo. Specifically, the C-terminus of Ptch1 harbors motifs encoding Class I and II SH3-binding sites. SH3-domain binding activity was verified using GST-c-src(SH3), -Grb2(SH3) and -p85β(SH3) fusion-proteins. Ectopically-expressed Grb2 or p85β could also be co-immunoprecipitated with the Ptch1 C-terminus. Addition of Shh to serum-starved human mammary epithelial cells and Shh Light II fibroblasts stimulated phosphorylation of Erk1/2. Erk1/2 activation was observed in cells where Smo activity had been inhibited using cyclopamine and in the breast epithelial cell line, MCF10A, that does not express Smo. These data reveal novel binding activities for the C-terminal region of Ptch1 and define a signalling pathway stimulated by the Hh-ligands operating independently of pathways requiring Smo.